Electronic and interface properties of polyfluorene films on GaN for hybrid optoelectronic applications - Itskos, Grigorios; Xristodoulou, X.; Iliopoulos, Eleftherios; Ladas, Spyridon; Kennou, Stella; Neophytou, Marios; Choulis, Stelios A. (My University, 2013)
Electronic and interface properties of spin-coated poly(9,9- dioctylfluorenyl-2,7-diyl) (PFO) films on GaN have been investigated in terms of their potential for optoelectronic applications. The PFO/GaN interface was studied by photoemission spectroscopy showing a type-II energy alignment with band offsets suitable for efficient photocurrent generation. The light harvesting potential is further supported by fluorescence experiments that show evidence of photo-induced electron transfer from PFO to GaN. The impact of polymer film thickness was probed using emission anisotropy and ellipsometry, indicating the presence of an ordered planar phase of PFO. The study has implications to hybrid optoelectronic devices employing the two important materials.
Keywords: Optoelectronic applications; Interfaces (materials); Polyfluorene films